Deep brain stimulation for neuropathic cephalalgia. - Green, A; Owen, S; Davies, P; Moir, L; Aziz, T (2006)
The aim of this study was to determine the efficacy of deep brain stimulation (DBS) in the treatment of various types of intractable head and facial pains. Seven patients underwent the insertion of DBS electrodes into the periventricular/periaqueductal grey region and/or the ventroposteromedial nucleus of the thalamus. We have shown statistically significant improvement in pain scores (visual analogue and McGill's) as well as health-related quality of life (SF-36v2) following surgery. There is wide variability in patient outcomes but, overall, DBS can be an effective treatment. Our results are compared with the published literature and electrode position for effective analgesia is discussed.